Localization of self-generated synthetic footstep sounds on different walked-upon materials through headphones. Issue 1 (March 2016) - Turchet, Luca; Spagnol, Simone; Geronazzo, Michele; Avanzini, Federico
Abstract This paper focuses on the localization of footstep sounds interactively generated during walking and provided through headphones. Three distinct experiments were conducted in a laboratory involving a pair of sandals enhanced with pressure sensors and a footstep synthesizer capable of simulating two typologies of surface materials: solid (e.g., wood) and aggregate (e.g., gravel). Different sound delivery methods (mono, stereo, binaural) as well as several surface materials, in the presence or absence of concurrent contextual auditory information provided as soundscapes, were evaluated in a vertical localization task. Results showed that solid surfaces were localized significantly farther from the walker's feet than the aggregate ones. This effect was independent of the used rendering technique, of the presence of soundscapes, and of merely temporal or spectral attributes of sound. The effect is hypothesized to be due to a semantic conflict between auditory and haptic information such that the higher the semantic incongruence the greater the distance of the perceived sound source from the feet. The presented results contribute to the development of further knowledge toward a basis for the design of continuous multimodal feedback in virtual reality applications .